2009
DOI: 10.1158/1055-9965.epi-08-0743
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Microarray Validation: A Methodologic Study with Special Reference to Lung Cancer

Abstract: Background: Although tissue microarray (TMA) studies of histopathologic material have been frequently reported in studies of malignant diseases, the question of sample size (i.e., the diameter and the number of tissue cylinders investigated) has been rarely discussed. This study addresses the methodologic question of sample size in a variety of tumor types. Material and Methods: Material from 29 cases of lung carcinoma (small cell, squamous cell, and adenocarcinomas) was examined immunohistochemically for Ki-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Furthermore, TMA technology provides great economy of research resources, personnel, and tissue specimens. It is currently the technique of choice for high throughput research (15,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TMA technology provides great economy of research resources, personnel, and tissue specimens. It is currently the technique of choice for high throughput research (15,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…As the representativeness of the TMA plays a critical role particularly in focally expressed antigens, such as BCRP1, the TMA was prepared according to recent validation data in lung cancer and mesothelioma that demonstrated that three to four tissue cores per sample are sufficient to produce reliable results [35][36][37]. Moreover, in half of the cases, the results of the TMA were compared with corresponding whole tissue sections and showed full concordance.…”
Section: Discussionmentioning
confidence: 99%
“…We collected tissues by sampling one representative tissue core, 1 mm in diameter chosen from each formalin-fixed, paraffin-embedded tumor specimen (27)(28)(29)(30). The sections of tissue microarrays (TMAs) were dewaxed using xylene and rehydrated through graded alcohols.…”
Section: Methodsmentioning
confidence: 99%